ETHNOMATEMATICS EXPLORATION AT SIPAMUTUNG TEMPLE PADANG LAWAS REGENCY IN THE CONCEPT OF BUILDING SPACE - Daulay, Intan Sari; Yahfizham, Yahfizham (Prima: Jurnal Pendidikan Matematika, 2025)
Indonesia is a country rich in culture and historical heritage, one of which is the   sipamutung   temple located in Padang   old   regency. This temple not only holds cultural and spiritual values but also contains mathematical concepts that are interested to study in mathematics education. This study aims to explore and describe the mathematical concepts embedded in the architectural structure of   sipamutung   temple from the perspective of   ethnomathematics ,particularly focusing on solid geometry. This research employee a qualitative method with an ethnographic approach. Data were collected through direct observation, interviews with temple managers, and  photographic document of the research objects. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that the architectural structure of Sipamutung Temple Applies Various Geometric Shapes such as Cubes, Rectangular Prisms, Pyramids, Spheres, and Cylinders. These Geometric Elements are found in the main building, Stairs, Perwara, Inner Chambers, and Temple Ornaments. This study contributes to the development of mathematics learning based on local culture and raises awareness of the importance of cultural heritage preserving. Through an ethnomathematical approach, mathematics learning can be become more contextual, engaging, and meaningful for students.